Enhanced whale optimization algorithm for medical feature selection: A COVID-19 case study - Nadimi-Shahraki, Mohammad H.; Zamani, Hoda; Mirjalili, Seyedali (Computers in biology and medicine, 2022)
The whale optimization algorithm (WOA) is a prominent problem solver which is broadly applied to solve NP-hard problems such as feature selection. However, it and most of its variants suffer from low population diversity and poor search strategy. Introducing efficient strategies is highly demanded to mitigate these core drawbacks of WOA particularly for dealing with the feature selection problem. Therefore, this paper is devoted to proposing an enhanced whale optimization algorithm named E-WOA using a pooling mechanism and three effective search strategies named migrating, preferential selecting, and enriched encircling prey. The performance of E-WOA is evaluated and compared with well-known WOA variants to solve global optimization problems. The obtained results proved that the E-WOA outperforms WOA's variants. After E-WOA showed a sufficient performance, then, it was used to propose a binary E-WOA named BE-WOA to select effective features, particularly from medical datasets. The BE-WOA is validated using medical diseases datasets and compared with the latest high-performing optimization algorithms in terms of fitness, accuracy, sensitivity, precision, and number of features. Moreover, the BE-WOA is applied to detect coronavirus disease 2019 (COVID-19) disease. The experimental and statistical results prove the efficiency of the BE-WOA in searching the problem space and selecting the most effective features compared to comparative optimization algorithms. •Proposing an enhanced whale optimization algorithm (E-WOA) for global optimization.•Introducing a pooling mechanism and effective search strategies in E-WOA.•Introducing BE-WOA as the binary version of E-WOA for medical feature selection.•Comparing BE-WOA with state-of-the-art algorithms for selecting effective features.•E-WOA and BE-WOA algorithms are competitive and superior to comparative algorithms.